Contributions to the knowledge of the Slovenian intellectual "opposition" in the 1980s under the screening of the State Security Service - Šela, Ana (Annales. Series historia et sociologia, 2021)
The author discusses the entities that constituted the intellectual “opposition” in the 1980s in the Socialist Republic of Slovenia, the areas in which these entities operated and how they were treated by state authorities. Within the framework of cultural “opposition”, which was part of the intellectual “opposition”, the author discusses the significance of the alternative movements that began to appear more frequently in Slovenia in the 1980s. With different views and critiques of the former system, which they expressed through art, these entities had a strong influence on the Slovenian public at that time. Based on documents of the Slovenian secret political police, the State Security Service, kept in the Archives of the Republic of Slovenia (Arhiv Republike Slovenije), the author analyses the surveillance and control of the main intellectual “opposition” and alternative movements. With the aid of the archival documents and the existing scientific literature the author also discusses the role played by the intellectual “opposition” and new social movements and their influence on democratization and, ultimately, on the independence of Slovenia.
Keywords: alternative movements; alternativna gibanja; democratization; demokratizacija; eighties; intelektualna opozicija; intellectual opposition; Služba državne varnosti; Social Republic of Slovenia; Socialistična republika Slovenija; State Security Service